Responding to the Call: Building a Training Program to Diversify the Academy in Alzheimer's Disease Research - Ingram, Lucy Annang; Ford, Marvella E.; Johnson, Christiana L.; Ashford-Carroll, Brianna; McCollum, Quentin; Friedman, Daniela B.; Levkoff, Sue Ellen (Frontiers in Public Health, 2021)
Alzheimer’s disease and related dementias (ADRD) are at the forefront of the United States (US) public health agenda due to their tremendous human and financial burden. Further, disproportionately high ADRD rates among racial/ethnic minorities require incorporating the unique perspectives of racially and ethnically diverse scientists, which will necessitate diversifying the scientific workforce that investigates disparities in aging. The purpose of this paper is to describe the training and mentorship initiatives of the National Institute on Aging (NIA)-funded Center XXX, emphasizing lessons learned from our engagement with underrepresented minority and minoritized (URM) scientists. We highlight three aims of the Center’s training and mentorship component: (1) Fund pilot projects for URM Scientists conducting research on sociocultural, behavioral, and environmental factors that influence ADRD-related health disparities; (2) Provide mentorship to build the research capacity of Center Scientists; and (3) Offer research education in Health Disparities and Minority Aging Research to Center Scientists and interested researchers at all partner institutions. Our experience may be a practical resource for others developing interdisciplinary training programs to increase the pipeline of URM Scientists conducting ADRD research, with the ultimate goal of developing interventions to reduce ADRD disparities in the US.